Population genetic structure of Lactifluus deceptivus associated to oak forests (Quercus humboltii) in two regions of Colombia (2017)
ECtoMycorrhizal (ECM) fungi are symbiotic organisms that establish mutual associations between plant roots and fungal mycelia. The ectomycorrhizal fungus Lactifluus deceptivus is distributed in temperate rainforest of Andean cordilleras of Colombia associated with the host tree Quercus humboldtii. The genet size and population genetic structure of Lf. deceptivus associated to these forests has not been investigated yet. In this study, seven microsatellites markers were employed to characterize the genet size and to analyze the population genetic structure of Lf. deceptrvus from two forests in Boyacá and one forest in Santander. Bayesian cluster analysis, principal components analyses and Øst values strongly separated Boyacá populations from the population in Santander. Additionally, the population from Santander had a reduced gene flow when compared to populations from Boyacá. The studied populations of Lf. deceptivus showed strong differentiation and a decreased gene flow, both phenomena with a pattern of geographic isolation.